The Level of Professional and Personal Competencies and their Relationship to Job Satisfaction among Teachers of Students with Hearing Disabilities in the Light of some Variables - Islam Al-Jdoua; Hatem Al Khumra (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: The current study aimed at the level of professional and personal competencies and their relationship to job satisfaction among teachers of students with hearing disabilities in the light of some variables. Methods: The descriptive analytical approach was used through a sample of (80) male and female teachers. This is done by describing the socio-demographic characteristics of teachers of students with hearing disabilities and identifying the difficulties they face while dealing with this category.Additionally, the job satisfaction scale and the professional and personal competencies scale were used. Results: After conducting the statistical analysis process, the study concluded that there is a direct and statistically significant correlation between job satisfaction and professional and personal competencies among teachers of students with hearing disabilities, and there are no statistically significant differences at the level of significance (0,05>α) between job satisfaction It is due to the variables of gender, age and experience, and there are no statistically significant differences at the significance level (0,05>α) for professional and personal competencies due to the variables of gender, age and experience. Conclusions: The study recommended the need for the competent authorities to develop programs for people with hearing disabilities to develop their skills and provide them with the required social interaction, and the need to train parents of children with hearing disabilities, and encourage them to train their children with hearing disabilities at home.